CLOUD-BASED BIGBLUEBUTTON IMPLEMENTATION SUPPORTS VIRTUAL MEETINGS AT RRI MEDAN - Muhammad Rifqi Sakti; Akhyar Lubis (Department of Computer Engineering, Universitas Wiralodra, 2023)
Virtual meetings have become an important necessity in today's digital era, especially in the midst of the COVID-19 pandemic which requires limiting physical contact. Various platforms exist to provide online meeting solutions. One platform that can be used for virtual meetings is the cloud-based BigBlueButton. This platform has been actively used in internal and external meetings, saving travel and time costs, as well as increasing work productivity and effectiveness. This research aims to implement BigBlueButton as a solution to support virtual meetings at RRI Medan. In this study, BigBlueButton is implemented using cloud infrastructure to increase system scalability and availability. Data collection methods used are direct observation, interviews, and secondary data collection. The results of the study show that the implementation of cloud-based BigBlueButton has succeeded in increasing the efficiency and flexibility of virtual meetings at RRI Medan. This study contributes to expanding understanding of the use of cloud-based BigBlueButton to support virtual meetings in the RRI Medan environment.